Analisis Efisiensi Penyimpanan Arsip Digital Berbasis ELVIS Pada PT. Kornet Logistics - Sultan Salahuddin Al Ayyubi; Darma Rika Swaramarinda; Suherdi Suherdi (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
. PT. Kornet Logistics is a company operating in the Logistics industry that uses the ELVIS system as an administrative tool. This study aims to identify and analyze the management process, efficiency levels, and factors influencing the efficiency of digital archive storage based on the ELVIS software in office administration at PT. Kornet Logistics. This study employs a descriptive qualitative approach. Data collection was conducted through observation, interviews, and documentation involving 5 (five) employee informants who use the system in their daily work. The research results conclude that the implementation of the ELVIS system at PT. Kornet Logistics is well-structured through access rights management tailored to employee positions and a systematic storage process. In terms of efficiency, the ELVIS system has proven highly effective in improving the speed and accuracy of document searches, reducing search time from hours to less than 5 minutes with the help of search filter features. This implementation has also had a positive impact on employees’ workspaces, which have become more organized as physical files can be directly transferred to the warehouse. The primary factor contributing to this efficiency is perceived ease of use, thanks to the system’s user-friendly interface. However, this efficiency still faces several obstacles, including a high reliance on internet stability, the occurrence of human error, and the fact that a fully paperless work environment has not yet been achieved due to regulations requiring physical printing for invoicing and a five-year document retention policy.